2021
DOI: 10.1055/a-1634-4710
|View full text |Cite
|
Sign up to set email alerts
|

Level of Diffusion and Training of Lung Ultrasound during the COVID-19 Pandemic – A National Online Italian Survey (ITALUS) from the Lung Ultrasound Working Group of the Italian Society of Anesthesia, Analgesia, Resuscitation, and Intensive Care (SIAARTI)

Abstract: Purpose The goal of this survey was to describe the use and diffusion of lung ultrasound (LUS), the level of training received before and during the COVID-19 pandemic, and the clinical impact LUS has had on COVID-19 cases in intensive care units (ICU) from February 2020 to May 2020. Materials and Methods The Italian Lung Ultrasound Survey (ITALUS) was a nationwide online survey proposed to Italian anesthesiologists and intensive care physicians carried out after the first wave of the COVID-19 pandemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…The percentage of daily user intensivists of the LUS score grew from less than 2% to 9%. The majority of the practitioners stated that the LUS influenced their clinical decisions (68%) and patient monitoring (73%) [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of daily user intensivists of the LUS score grew from less than 2% to 9%. The majority of the practitioners stated that the LUS influenced their clinical decisions (68%) and patient monitoring (73%) [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…A specific survey about LUS, named ITALUS, with 807 respondents, showed that LUS was extensively used during the first wave of the COVID-19 pandemic by anesthesiologists and intensive care physicians in Italy. However, 76.7% of this sample did not undertake any LUS certification [ 9 ].…”
mentioning
confidence: 99%
“…A recent online survey conducted by the International Society of Radiology showed that the current imaging practice of imaging in COVID-19 differs throughout the world: conventional chest X-ray and CT were the most applied imaging modalities, while LUS was used for bedside imaging and in the ICU, mostly by intensivists, usually using small mobile units for point-of-care ultrasound [67]. A survey conducted in Italy showed that LUS was already extensively used by anesthesiologists and intensivists at the time of the first wave of the COVID-19 pandemic and then, its adoption increased further [68] .…”
Section: The Use Of Lus In Covid-19 In Different Regions/countriesmentioning
confidence: 99%
“…Machines are robust, mobile, and potentially portable and require relatively little maintenance. Point-of-care ultrasound (POCUS) can assist emergency and critical care in COVID-19 management [68] and allows for utilization in out-of-hospital settings [69]. A low level of awareness of the many advantages of ultrasound technology mentioned above, and a lack of qualified staff adequately trained to perform LUS may be major barriers to its utilization, in particular for LMICs.…”
Section: The Use Of Lus In Covid-19 In Different Regions/countriesmentioning
confidence: 99%